Etika Berbusana Mahasiswa Pendidikan Agama Islam Perspekif Kode Etik IAIN Kediri - Nafi’ah, Istiana Malikatin; Anwar, Ali (Tribakti: Jurnal Pemikiran Keislaman, 2020)
This study discusses to study and analyze the styles worn by IAIN Kediri students in view of the Code of Ethics for student fashion styles to be the focus of this research. The Code of Ethics is the highest rule that all members must obey in this case are students and all leaders and lecturers. In fact the character of a fashionable student and never left with the times, there are already students aligning between reality and existing rules by dressing in accordance with the rules of this study so that students are found in accordance with the existing use jeans for students and shirts for students .